A Qualitative Analysis of Outpatient Medication Use in Community Settings: Observed Safety Vulnerabilities and Recommendations for Improved Patient Safety. Issue 4 (June 2021) - Lyson, Helena C.; Sharma, Anjana E.; Cherian, Roy; Patterson, Emily S.; McDonald, Kathryn M.; Lee, Shin-Yu; Sarkar, Urmimala
Abstract : Objective: The aim of the study was to analyze diverse patients' experiences throughout the medication use process to inform the development of overarching interventions that support safe medication use in community settings. Methods: Using a qualitative observational approach, we conducted approximately 18 hours of direct observation of the medication use process across multiple settings for a sample of vulnerable, high-risk patients. Observers recorded detailed field notes during the observations. To enrich the observational findings, we also conducted six semistructured interviews with medication safety experts representing a diversity of perspectives. Barriers and facilitators to safe medication use were identified based on inductive coding of the data. Results: A variety of safety vulnerabilities plague all stages of the medication use process and many of the well-established evidence-based interventions aimed at improving the safety of medication use at key stages of the process have not been widely implemented in community settings observed in this study. Key safety vulnerabilities identified include: limited English proficiency, low health literacy, lack of clinician continuity, incomplete medication reconciliation and counseling, unsafe medication storage and disposal habits, and conflicting healthcare agendas with caregivers. Conclusions: Our findings underscore a need for overarching, comprehensive interventions that span the entire process of medication use, including integrated communication systems between clinicians, pharmacies, and patients, and a "patient navigator" program that assists patients in navigating the entire medication-taking process. Collective ownership of the medication management system and mutual motivation for devising collaborative solutions is needed among key sectors.